COMMENTS CONCERNING THE LABOUR MARKET IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2021)
There are three stages in human life: stage of gaining the knowledge and skills, time for provision of work and retirement age. The possibilites to retire are established by adequate legal regulations. In this study the consequences for the labour market due to the increase of retirement age have been discussed and the legal regulations have been proposed, in order to reduce considerable the unemployment rate.